2014
DOI: 10.1186/s13071-014-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of visceral leishmaniasis: a case control study in north-western Ethiopia

Abstract: BackgroundVisceral leishmaniasis (VL, also called ‘’kala-azar”), is a life threatening neglected tropical infectious disease which mainly affects the poorest of the poor. VL is prevalent in Ethiopia particularly in the northwest of the country. Understanding the risk factors of VL infection helps in its prevention and control. The aim of the present study was to identify the factors associated with VL.MethodsA case–control study was carried out during the period of January-July 2013 in northwest Ethiopia. Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
9
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
10
34
9
3
Order By: Relevance
“…This was consistent with studies in Colombia and Ethiopia, which reported that the increased frequency of droughts is likely to increase the incidence of the disease [45, 46]. In dry conditions like droughts, people in rural areas cluster around water supplies because of the limited water sources, exposing them to a high concentration of vector populations.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with studies in Colombia and Ethiopia, which reported that the increased frequency of droughts is likely to increase the incidence of the disease [45, 46]. In dry conditions like droughts, people in rural areas cluster around water supplies because of the limited water sources, exposing them to a high concentration of vector populations.…”
Section: Discussionsupporting
confidence: 90%
“…Los dos últimos factores se han relacionado en otros estudios con el riesgo de transmisión vectorial rural y urbana, pues aumentan las fuentes de atracción del insecto, su acceso a humanos y perros, y una menor eficiencia de los repelentes espaciales domiciliarios (18,(27)(28)(29).…”
Section: Discussionunclassified
“…Environmental change will often modify the transmission patterns of vector-borne diseases, through its effects at different ecological scales. Improving vegetation types and climate condition were favored to increase vector densities or host-vector contacts and reintroductions of pathogens, or breakdown of vector control measures (Yared et al, 2014). The existing major agricultural schemes, ongoing and planned mega-projects such as sugar industries and sugar cane farming, dams for electricity/irrigation purposes and expansion of irrigation and/or rain fed agriculture both by small scale farmers and large scale investors all exist within the lower Kola to Weina Dega agro-ecological zones.…”
Section: Epidemiological Changes Of Leishmaniasis Environmental Changmentioning
confidence: 99%
“…Poor housing and sanitary conditions such as lack of waste management, open sewerage and poor health facilities are an indication of poverty. Thus poverty increases the risk of VL through increasing the breeding of sand flies and their access to people (Yared et al, 2014;Hailu et al, 2016). Moreover, low educational level and socioeconomic concerns also increases risks of both VL and CL in the country (Dawit et al, 2013).…”
Section: Knowledge and Socio-economic Factorsmentioning
confidence: 99%